Management of acute ischaemic stroke in patients with dementia. (2nd February 2017) - Subic, A.; Cermakova, P.; Norrving, B.; Winblad, B.; von Euler, M.; Kramberger, M. G.; Eriksdotter, M.; Garcia‐Ptacek, S.
Abstract: An estimated 10% of stroke patients have an underlying dementia. As a consequence, health professionals often face the challenge of managing patients with dementia presenting with an acute stroke. Patients with dementia are less likely to receive thrombolysis (0.56–10% vs. 1–16% thrombolysis rates in the general population), be admitted to a stroke unit or receive some types of care. Anticoagulation for secondary stroke prevention is sometimes withheld, despite dementia not being listed as an exclusion criterion in current guidelines. Studies in this population are scarce, and results have been contradictory. Three observational studies have examined intravenous thrombolysis for treatment of acute ischaemic stroke in patients with dementia. In the two largest matched case–control studies, there were no significant differences between patients with and without dementia in the risks of intracerebral haemorrhage or mortality. The risk of intracerebral haemorrhage ranged between 14% and 19% for patients with dementia. Studies of other interventions for stroke are lacking for this population. Patients with dementia are less likely to be discharged home compared with controls (19% vs. 41%) and more likely to be disabled (64% vs. 59%) or die during hospitalization (22% vs. 11%). The aim of this review was to summarize current knowledge about the management of ischaemic stroke in patients with pre‐existing dementia, including organizational aspects of stroke care, intravenous thrombolysis, access to stroke unit care and use of supportive treatment. Evidence to support anticoagulation for secondary prevention of stroke in patients with atrial fibrillation and antiplatelet therapy in nonembolic stroke will be discussed, as well as rehabilitation and how these factors influence patient outcomes. Finally, ethical issues, knowledge gaps and pathways for future research will be considered.